Aplikasi Pencarian Dokter di Kota Padang Berbasis Mobile - Yance Sonatha; Ervan Asri; Indri Rahmayuni (ISB Atma Luhur, 2021)
Nowadays people have started to realize the importance of health. Everyone wants to quickly find out where the right doctor is if they want to get health services or have shown certain symptoms of illness. This research resulted in an application called